2019
DOI: 10.3389/fnins.2019.01269
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Theta-Band Local Field Potential Oscillations Across Brain Networks With Central Thalamic Deep Brain Stimulation to Enhance Spatial Working Memory

Abstract: Deep brain stimulation (DBS) is a well-established technique for the treatment of movement and psychiatric disorders through the modulation of neural oscillatory activity and synaptic plasticity. The central thalamus (CT) has been indicated as a potential target for stimulation to enhance memory. However, the mechanisms underlying local field potential (LFP) oscillations and memory enhancement by CT-DBS remain unknown. In this study, we used CT-DBS to investigate the mechanisms underlying the changes in oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Despite these distinctions, improved arousal and facilitation of behavior have been reported for electrical stimulation of both CL and Cm-Pf. In rodent studies, electrical stimulation of CL facilitates object recognition memory 22 , working memory 25 and decision-making 23 , 24 . In healthy NHPs, CL dominant stimulation, that includes the DTTm as shown here, facilitates sustained attention, working memory, and pattern-recognition behaviors 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these distinctions, improved arousal and facilitation of behavior have been reported for electrical stimulation of both CL and Cm-Pf. In rodent studies, electrical stimulation of CL facilitates object recognition memory 22 , working memory 25 and decision-making 23 , 24 . In healthy NHPs, CL dominant stimulation, that includes the DTTm as shown here, facilitates sustained attention, working memory, and pattern-recognition behaviors 35 .…”
Section: Discussionmentioning
confidence: 99%
“…DBS of the subthalamic nucleus (STN) and globus pallidus interna (GPi) was shown to effectively reduce pathological β band activity (13-30 Hz) in the corticothalamic-basal ganglia network responsible for hallmark Parkinsonian rhythms (Müller and Robinson, 2018). Central thalamus-DBS (CT-DBS) increased hippocampal θ oscillations and improved SWM in SD rats (Chang et al, 2019), and ventral internal capsule/ventral striatum DBS therapy increased mPFC θ oscillations and improved cognitive control in human subjects with MDD Obsessive Compulsory Disorder (Widge et al, 2019). Recent work further demonstrated that acute DBS in the mPFC with 130 Hz improved mPFC-vHPC θ and γ coupling in a rat model of developmental schizophrenia (Lippmann et al, 2021).…”
Section: Brain Stimulationmentioning
confidence: 99%
“…Increased HPC-mPFC θ asynchrony and atypical γ oscillations associated with cognitive impairments. (Bowie and Harvey, 2006;Chang et al, 2019;Choi et al, 2016;Skirzewski et al, 2018) 768…”
Section: Rodent and Humanmentioning
confidence: 99%
“…Therefore, fixed frequency stimulation plans can be created that are able to be used by potentially all patients. While fixed frequency stimulation provides an approach that is able to be applied generally to patients, theories regarding the mechanism by which DBS affects neuronal networks underlying memory are varied, and even contradictory ( Tan et al, 2020 )—ranging from enhancing brain states associated with successful memory function ( Hanslmayr and Roux, 2017 ), to enhancing theta ( Chang et al, 2019 ) or gamma ( Kucewicz et al, 2018 ) oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for differing, or a combination, of mechanisms depending on the location and type of stimulation applied may explain why approaches using fixed frequency stimulations have met with mixed success, with some groups reporting no effect when stimulating hippocampus directly ( Jacobs et al, 2016 ; Tan et al, 2020 ), while other groups that have shown success are dependent on a combination of differences of electrode placement, frequency and other stimulation parameters ( Hanslmayr and Roux, 2017 ; Chang et al, 2019 ; Mankin and Fried, 2020 ; Mohan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%